2004
DOI: 10.1007/s11101-004-4155-9
|View full text |Cite
|
Sign up to set email alerts
|

Volatile halogenated metabolites from marine red algae

Abstract: A significant number of halogenated low molecular weight metabolites have exhibited an impressive array of biological properties ranging from antimicrobial to insecticidal activities. Studies on the natural products chemistry of the red seaweeds were recently stimulated by the discovery of the acyclic monoterpene halomon, which exhibits selective antitumor activity in the National Cancer Institute's human tumor and disease oriented in vitro screen.The present review is a taxonomy based compilation of the avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
108
0
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(121 citation statements)
references
References 131 publications
(136 reference statements)
0
108
0
10
Order By: Relevance
“…The anthropogenically produced gas concentrations are noted ''1'' for similar reasons. Other references are as follows: (2) Hallenbeck and Benemann (2002); (3) Anderson and Levine (1986); (4) Ryter and Otterbein (2004); (5) Wentworth et al (2003); (6) Paul and Pohnert (2011); (7) Monson et al (2012); (8) Belay and Daniels (1987); (9) Pyysalo (1976); (10) Vitousek et al (2013); (11) Belser (1979); (12) Gribble (2003); (13) Kuhn et al (2000); (14) Nightingale et al (1995); (15) Kladi et al (2004); (16) Watts (2000); (17) Ballschmiter (2003); (18) Finster (2008); (19) Geng and Mu (2006). Columns are IUPAC name, molecular formula, SMILES description, molecular weight, boiling point (e = experimentally measured, p = predicted), production by life (Y/N), and references for molecules produced by life.…”
Section: Discussionmentioning
confidence: 99%
“…The anthropogenically produced gas concentrations are noted ''1'' for similar reasons. Other references are as follows: (2) Hallenbeck and Benemann (2002); (3) Anderson and Levine (1986); (4) Ryter and Otterbein (2004); (5) Wentworth et al (2003); (6) Paul and Pohnert (2011); (7) Monson et al (2012); (8) Belay and Daniels (1987); (9) Pyysalo (1976); (10) Vitousek et al (2013); (11) Belser (1979); (12) Gribble (2003); (13) Kuhn et al (2000); (14) Nightingale et al (1995); (15) Kladi et al (2004); (16) Watts (2000); (17) Ballschmiter (2003); (18) Finster (2008); (19) Geng and Mu (2006). Columns are IUPAC name, molecular formula, SMILES description, molecular weight, boiling point (e = experimentally measured, p = predicted), production by life (Y/N), and references for molecules produced by life.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the most frequently reported halometabolites are produced by marine red algae (Rhodophyceae) and include halogenated indoles, terpenes, acetylenes, phenols, and volatile hydrocarbons (9,10,15,18,19). Among the red, brown, and green algae, Rhydophyta are * This work was supported, in whole or in part, by National Institutes of Health Grant AI52445 (to B. S. M.) and by Ruth L. Kirschstein National Research Service Award GM067550 from the National Institutes of Health Training Program in Marine Biotechnology at the Scripps Institution of Oceanography (to J. M. W.).…”
Section: Vanadium Haloperoxidasesmentioning
confidence: 99%
“…Specifically, the culturing of Hypnea spinella (Rhodophyta, Hypneaceae) and Halopithys incurva (Rhodophyta, Rhodomelaceae) have recently gained interest due to their production of metabolites with antimicrobial and antifungal activities. H. incurva synthesizes 2,3-dibromo-4,5-dihydroxybenzyl alcohol (lanosol), which has been shown to have high toxic effects on bacteria and other algae (Kladi et al 2004). Furthermore, it has been reported that extracts from H. incurva exert antimicrobial activity against Staphylococcus aureus MB5393 (González del Val et al 2001).…”
Section: Introductionmentioning
confidence: 99%